Should the law on assisted dying be changed? No. (21st April 2011) - Fitzpatrick, Kevin
Abstract : Raymond Tallis ( doi:10.1136/bmj.d2355 ) argues that allowing terminally ill people to choose an assisted death is part of good care, but Kevin Fitzpatrick believes it will endanger the lives of disabled people